Identification of a SARS-CoV-2 virus-derived vmiRNA in COVID-19 patients holding potential as a diagnostic biomarker - Zhao, Qian; Lü, Jinhui; Zhao, Bing; Guo, Yuefan; Wang, Qiong; Yu, Shanshan; Hao, Lipeng; Zhu, Xiaoping; Yu, Zuoren (Frontiers in Cellular and Infection Microbiology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a lasting threat to public health. To minimize the viral spread, it is essential to develop more reliable approaches for early diagnosis of the infection and immediate suppression of the viral replication. Herein, through computational prediction of SARS-CoV-2 genome and screening analysis of specimens from covid-19 patients, we predicted 15 precursors for SARS-CoV-2-encoded miRNAs (CvmiRNAs) containing 20 mature CvmiRNAs, in which CvmiR-2 was successfully detected by quantitative analysis in both serum and nasal swab samples of patients. CvmiR-2 showed high specificity in distinguishing covid-19 patients from normal controls, and high conservation between SARS-CoV-2 and its mutants. A positive correlation was observed between the CvmiR-2 expression level and the severity of patients. The biogenesis and expression of CvmiR-2 were validated in the pre-CvmiR-2-transfected A549 cells, showing a dose-dependent pattern. The sequence of CvmiR-2 was validated by sequencing analysis of human cells infected by either SARS-CoV-2 or pre-CvmiR-2. Target gene prediction analysis suggested CvmiR-2 may be involved in the regulation of the immune response, muscle pain and/or neurological disorders in covid-19 patients. In conclusion, the current study identified a novel v-miRNA encoded by SARS-CoV-2 upon infection of human cells, which holds the potential to serve as a diagnostic biomarker or a therapeutic target in clinic.